HUBUNGAN DISCHARGE PLANNING SESUAI PROSEDUR DI RUMAH SAKIT DENGAN PERAWATAN RUMAH PASIEN STROKE DI POLIKLINIK RSSN BUKITTINGGI TAHUN 2014 - Ernalinda Rosya; Amana Vera; Aldo Yuliano (JURNAL KESEHATAN PERINTIS, 2015)
Stroke patients rely more on family support in home care. One way to improve the behavior of the family by providing discharge planning, in order to family contact and counseling more intensive. The purpose of this research to determine the influence of discharge planning to Family Behaviour in Homes Care Stroke Patients Visits at the RSSN Bukittinggi 2014. This research was desain deskriktif korelatif with cross sectional and the number of respondents 86 people, using statistics technique from 14 July to 25 August 2014. Collecting data using questionnaires and direct observations of the respondents were in the univariate and bivariate analyzes. Univariate analysis showed better results than most of the respondents (54.7%) of respondents yes conduct discharge planning according to SOP, most respondents (51.2%) to be done, of the respondents have in the treatment of post-stroke patients at home after being given personal education and the analysis of the chi-squqre test with significance level of knowledge (p = 0.004) of respondents indicated that no personal Relationship of discharge planning according to the procedure at the hospital with treatment homes stroke patients national hospital stroke of Bukittinggi to be able to make discharge planning as a routine program to families and patients with stroke as a health recovery efforts post-stroke patients.